Cu2ZnSnSe4 QDs sensitized electrospun porous TiO2 nanofibers as photoanode for high performance QDSC. (1st September 2018) - Singh, Nisha; Murugadoss, Vignesh; Nemala, Sivasankar; Mallick, Sudhanshu; Angaiah, Subramania
Graphical abstract: Highlights: The Cu2 ZnSnSe4 QDs was prepared by hot-injection method at low temperature. Obtained narrow sizes of ∼5 nm with light absorption onset about ∼1100 nm. Attained the PCE (η) of 3.61% for Cu2 ZnSnSe4 QDs sensitized porous TiO2 NFs based QDSC. Abstract: An earth-abundant and relatively less toxic, quaternary Cu2 ZnSnSe4 (CZTSe) quantum dots (QDs) were prepared by hot injection method at low temperature to use as a sensitizer for QDSC. The formation of tetragonal phase and stoichiometry were confirmed by X-ray diffraction (XRD), Raman spectroscopy and energy dispersive X-ray (EDX) analysis, respectively. The UV–Vis-NIR and photoluminescence spectroscopy was used to determine the bandgap (1.66 eV) and narrow emission (1050–1130 nm) range. Moreover, transmission electron microscopy (TEM) was used to find out the average size of CZTSe QDs and it was found to be ∼5 nm. It can highly adsorb on the porous TiO2 nanofibers (NFs) and enhance the absorbance due to its smaller size. The photoconversion efficiency was investigated using the prepared CZTSe QDs sensitized porous TiO2 NFs based QDSC and its photoconversion efficiency (PCE) was found to be 3.61% which is higher than that of the conventional TiO2 NFs based QDSC (η ≈ 2.84%).